Living Qur’an sebagai Solusi Penguatan Pendidikan Akhlak terhadap Siswa: Perspektif Teori Thomas Lickona (Studi Kasus MTs Pesantren El-Madani Rawalo) - Winasih, Tia Mugi; Munfarida, Elya (Jurnal Kependidikan, 2024)
Abstract Currently, the Living Qur'an is dominated by the scope of social research, namely the scope of the community in wider society. Formal education, especially in secondary schools, still rarely incorporates and preserves the Al-Qur'an in it, whether it is for the development of children's character, moral and spiritual values. In fact, the "spirit" of Islamic education lies in efforts to embody the Koran and practice it well in the school and community environment. In this research the author analyzes Lickona's educational theory of thought as "reinforcing research results". Namely, the study of the living Qur'an includes moral feeling, moral coming and moral acting in MTs educational institutions. The research writer used a qualitative approach, using the case study method with the research object at MTs Pesantren El-Madani Rawalo. The sources for this research are primary and secondary, participation from the resource persons, namely Mr. Abdul Basit (Principal of the school), Mr. Ahsin (Tahfiz teacher), Mrs. Khilya and students in grades 7-8. Data collection using individual in-depth interviews. With field research and conclusions drawn. According to the results obtained, the analysis of the living Qur'an at Mts from a lickon perspective is emphasized for students from grades 7 - 8, namely there are three most important aspects: understanding, knowing and applying it by students in everyday life. Therefore, students do not just carry out Islamic teachings but also become aware of knowledge, experience and appreciation. Keywords: Living Quran, Students, Spiritual Education, Thomas Lickona. Abstrak Living Qur’an dimasa ini di dominasikan dalam ruang lingkup penelitian sosial, yakni lingkup komunitas di masyarakat luas. Pendidikan formal terutama di pendidikan sekolah menengah masih jarang membumikan dan melestarikan Al-qur’an di dalamnya, entah terhadap pengembangan nilai karakter, moral dan keruhanian anak. Padahal “ruh” pendidikan Islam terdapat pada pengupayaan penjiwaan al-qur’an dan mempraktikan secara baik di lingkungan sekolah serta masyarakat. Dalam penelitian ini penulis menganalisis teori pendidikan pemikiran Thomas lickona sebagai “penguat hasil penelitian”. Yaitu kajian living qur’an meliputi moral feeling, moral knowing serta moral acting di lembaga pendidikan MTs, penulis meneliti dengan menggunakan pendekatan kualitatif, menggunakan metode studi kasus dengan objek penelitian di MTs Pesantren El-Madani Rawalo. Sumber dari penelitian ini adalah primer serta sekunder, partisipasi dari narasumber yakni bapak abdul basit (Kepala sekolah), bapak ahsin (Guru tahfiz), ibu khilya, dan siswa kelas 7-8. Pengumpulan data dengan wawancara mendalam secara individual, dengan penetian lapang dan ditarik menggunakan kesimpulan. Sesuai hasil yang didapatkan bahwanya analisa living qur’an di MTs Pesantren El Madani Rawalo dari perspektif lickon akan ditekankan pada siswaa sejak kelas 7 sampai selesai, ada tiga aspek terpenting di dalamnya yaitu: menghayati, mengetahui serta diterapkan oleh siswa dalam kehidupan sehari-hari . Oleh karen itu siswa tidak sekedar menjalankan ajaran Islam saja melainkan kesadaran pengetahuan, pengalaman dan penghayatan. Kata Kunci : Living Qur’an, Siswa, Pendidikan Ruhani, Thomas Lickkona